Ovine pneumonia due to Mycoplasma agalactiae - MONDAL, D; SRIVASTAVA, M K (The Indian Journal of Animal Sciences, 2014)
Nasal swab samples (40) collected from pneumonic lambs, aged between 5-10 weeks and bacteriologically cultivated in PPLO broth and agar. Biochemical characterization and growth inhibition test of the 6 isolates were conducted which identified the causative agent as Mycoplasma agalactiae. Antibiotic disc sensitivity test with 12 different antibacterials revealed that the isolates were highly sensitive to enrofloxacin, oxytetracycline, ciprofloxacin, gentamycin and furazolidone. Experimental inoculation with the pure culture provided similar clinical signs to lambs.